Nitrogen recovery by urea hydrolysis and struvite precipitation from anthropogenic urine - Kabdaşli, I.; Tünay, O.; Işlek, C.; Erdinç, E.; Hüskalar, S.; Tatli, M B. (IWA Publishing, 2006)
Human urine is a source of nutrients and has a significant potential for recycle of nitrogen. Recently, much research focused on separate collection and treatment of human urine. Recovery of nutrients from human urine requires hydrolysis of urea into ammonia and subsequent removal of ammonia and sometimes phosphorus. This study attempted to evaluate urea hydrolysis of human urine in both untreated fresh samples and urease added urine samples. Recovery of nutrients by struvite precipitation on pre-hydrolysed samples was also assessed on undiluted and 1:1 diluted samples. Results of urea hydrolysis on untreated urine samples indicated that the process was slow and pH exerted a significant effect on the process. No hydrolysis occurred above pH 10. From pH 2 to 7.5, 25% of urea could be hydrolysed in 30 d. Urease added hydrolysis with the enzyme doses 25–49 mg L−1 was a rapid process providing complete conversion into ammonia in 1.5 h. Struvite precipitation conducted on enzyme hydrolysed urine sample proved to be an efficient process and ammonia removals up to 95% were obtained. Struvite precipitation also provided 50% organic nitrogen removal.
Keywords: Titanium; Nitrogen; Hydrolysis; Hydrogen-Ion Concentration; Urine; Urease; Chemical Precipitation; Humans; Urea